Geographical Information System in Planning the Orthodontist Need: A Pilot Study - Eren İşman; Savas Durduran; Zafer Sari (Galenos Yayinevi, 2013)
Objective:The purpose of this study is to evaluate the geographical distribution of all orthodontic patients who applied to Selcuk University Faculty of Dentistry Department of Orthodontics (SUDO) between 2000 and 2005.Materials and Method:Data in this study were obtained from computer records of patients who applied to SUDO between 2000 and 2005. Data were integrated into Arcview 3.3 geographical information system (GIS) software. By adding patient address data to the numeric maps of Turkey used in the GIS, spatial queries could be determined and spatial maps showing the geographical distribution of patients applying to SUDO were obtained.Results:The records of 9191 patients from 48 cities who applied for treatment to SUDO were examined. Distribution of patients' addresses by city was investigated. Accordingly, the highest demand for treatment was from Konya at 66.9% (1000-6147); second, the neighboring cities of Afyon at 0.76%, Karaman at 0.71%, and Aksaray at 0.57% (500-1000); third, Kutahya at 0.36% (250-500); fourth, Nigde at 0.20% (100-250); and fifth, Antalya at 0.09% and Nevsehir at 0.07% (50-100).Conclusion:The findings show that not only local patients but also a significant number of patients from other cities applied for a treatment to SUDO. Therefore, the situation identified by the GIS method will be a reference point for the officials and authorities who are making plans related to the number of patients seeking orthodontic treatment.